Development of a methodology for impact assessment of transport policies in cities (2018)
"This dissertation provides concepts and a methodological approach to assess impacts of transport expanding the traditional scope of the engineering discipline. Initially, it is made a historical analysis of the evolution of transport policies, the perspectives of the interventions and their stages in the development of cities. In addition, it makes a detailed description of a set of references about the impacts of policies and the definition of their scope, identifying triggers of change in usersþ behaviour.In this research the state of the art is amplified providing analytical concepts to perform assessments of distributional effects, whose scope is multidimensional in terms of time, spatial and groups of population. To do this, the proposal integrates econometrics tools and well-known techniques for longitudinal analysis using cross-sectional and panel data. The main part of this dissertation explains the guidelines for transport impact assessment procedures based on OLS with fixed effects, Diff- Diff with Propensity Score Matching and Time Series Analysis.Then, it is made a description of the databases management and standardization of available sources of travel information, as well as, the definition of comparable scenarios between populations.Two cases of specific transport policy measures are presented, making the respective assessment of transport policies implemented in the city of Bogotá in the last 20 years. It is described the structure of the information, the analytical models and the results obtained."--Tomado del Formato de Documento de Grado